Wear behavior of CADI operating under different tribosystems - Laino, Sebastian (2010)
A new type of Austempered Ductile Iron (ADI) containing free carbides in its microstructure, called Carbidic ADI (CADI), has been purposely designed for applications requiring high levels of abrasion resistance, but still keeping impact toughness. Nevertheless, wear resistance is strongly dependent on the tribosystem, and this is clearly noticed for the abrasive wear mechanism. In earlier investigations, the authors used the low stress abrasion condition imposed by the ASTM G 65 standard for laboratory tests. Therefore, this study is intended to evaluate CADI wear resistance by means of field trials under different abrasion conditions. Apart from the additional laboratory tests indicated by the ASTM G 65 standard, two CADI prototype parts were evaluated: screw segments for animal food extruders, whose abrasion severity is considered of low stress type (similar to that imposed in the laboratory), and wheel loader bucket edges, whose abrasion severity is considered of high stress type. The results gathered have demonstrated that CADI behaves satisfactorily under low stress abrasion conditions, though performance is poor under high stress conditions. To justify the differences in wear behavior, the worn surfaces were studied by microscopy, and also scratch tests were performed in order to evaluate the interaction between the abrasive particles and the microstructure. It was found that the good performance is obtained when the groove size is smaller than the average carbide size, and that under this condition abrasion resistance increases with the increase in the carbide content and hardness. Contrarily, when the groove size is greater than that of carbides, the performance is impoverished with the increase in the carbide content.